Knowledge, attitudes, practices of teenagers on sexual health in the district of Ambohidratrimo - Rafamantanantsoa, Jean F.; Ramontalambo, Tantely J.; Randriananahirana, Zina A.; Rakotoarison, Cathérine N. R.; Rakotovao, Andriamiadana L.; Rakotonirina, Julio (International Journal of Research in Medical Sciences, 2021)
Background: Talking about sex, sexuality, sexual health in many countries, including Madagascar, is very difficult because of the sacred and taboos that surround these questions but especially because of certain puritanism. The objective of this study was to assess the knowledge, attitudes and practices of adolescents in matters of sexual health. Methods: A retrospective, descriptive cross-sectional study was carried out in adolescents aged 10 to 19 seen in Ambohidratrimo district. The data were collected during the month of June and July 2019 and relate to data for the twelve months before the survey. Results: A total of 210 adolescents were recruited whose average age was 15.82±2.75 years and the sex ratio was 1:04. Eighty-six percent of the adolescents surveyed had heard of sexual health. Nine out of 10 adolescents would go to a health worker if they contract an STI. Almost a quarter or 23.8% of respondents declared having already had sexual intercourse. Conclusions: At the end of this study on the knowledge, attitudes and practices of adolescents on sexual health, they certainly have knowledge but considered average. Therefore, there is a need for sexuality education, for improving knowledge and understanding of sexual development, human procreation, healthy and adapted sexual behavior and different means of contraception, on the part of adolescents, but also with the aim of improving communications between adolescents and their parent.